Characterization of vaginal immune response to a polypropylene mesh: Diabetic vs. normoglycemic conditions. (15th April 2022) - Liang, Rui; Fisk, Abigail; King, Gabrielle; Meyn, Leslie; Xiao, Xiangwei; Moalli, Pamela
Abstract: Objective: Urogynecology meshes, typically manufactured from polypropylene, are widely used in the surgical treatment of stress urinary incontinence and pelvic organ prolapse. However, mesh-associated complications such as mesh exposure can develop in women undergoing mesh implantation, for which diabetes is an independent risk factor. We aimed to define the impact of diabetes on the vaginal immune response to mesh by comparing diabetic vs. normoglycemic conditions longitudinally in a rat sacrocolpopexy model. Methods: Diabetes (blood glucose ≥ 300 mg/dL) was induced in middle-aged female Wistar rats with streptozotocin (STZ). A polypropylene mesh was implanted on the vagina via modified sacrocolpopexy following bilateral ovariectomy and supracervical hysterectomy for 3-, 7-, and 42-days. Sham-operated controls underwent the same procedures without mesh. Mesh-associated inflammation, immune cell populations and cytokine/chemokine profiles were examined in the excised vaginal tissues. Results: Diabetes was reliably induced starting on the 3rd day following STZ injection. Under both normoglycemic and diabetic conditions, mesh caused a prolonged inflammatory response in the vagina with increased proinflammatory chemokines MCP-1 and MIP-1α as compared to Sham. Major differences between the two conditions were found at the later stage (42 days post-surgery), including an increased inflammation with larger foreign body granuloma and more giant cells at the mesh-tissue interface, increased fraction of macrophages in the immune cell population, and higher proinflammatory chemokine IP-10 in the diabetic group. Conclusion: Polypropylene mesh implanted on the vagina induces prolonged inflammation at the mesh-tissue interface. Diabetes increases the mesh-associated inflammation in the long term, which is related to a dysregulated macrophage response. Statement of significance: This study investigated the mechanism underlying the increased risk in women with diabetes for developing mesh complications such as mesh exposure. The significance includes: (1) it is the first study investigating vaginal host response to a prosthesis under the influence of diabetes; (2) the longitudinal study design elucidated the dynamic changes of vaginal immune response to mesh from very early to late stages; (3) our findings may inform future mechanistic studies and studies investigating preventive/therapeutic strategies to improve the outcomes of women with diabetes receiving vaginal implants. Graphical abstract: Image, graphical abstract